2020
DOI: 10.1371/journal.pone.0239657
|View full text |Cite
|
Sign up to set email alerts
|

Eps15 Homology Domain Protein 4 (EHD4) is required for Eps15 Homology Domain Protein 1 (EHD1)-mediated endosomal recruitment and fission

Abstract: Upon internalization, receptors are trafficked to sorting endosomes (SE) where they undergo sorting and are then packaged into budding vesicles that undergo fission and transport within the cell. Eps15 Homology Domain Protein 1 (EHD1), the best-characterized member of the Eps15 Homology Domain Protein (EHD) family, has been implicated in catalyzing the fission process that releases endosome-derived vesicles for recycling to the plasma membrane. Indeed, recent studies suggest that upon receptor-mediated interna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 75 publications
0
11
0
Order By: Relevance
“…Given the role of both EHD1 and EHD3 in regulating primary ciliogenesis, 13,20 it was somewhat unexpected that our previous study in RPE‐1 cells suggested that both remaining EHD paralogs, EHD4 and EHD2, appeared to be dispensable for primary ciliogenesis. Whereas EHD2 is an “outlier” with the least sequence identity and functional homology within the EHD‐family proteins, 37 EHD4 coordinates endosomal fission and recycling through its interactions with EHD1 29,30 and thus we initially chose to more extensively evaluate its potential role in regulating generation of the primary cilium.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the role of both EHD1 and EHD3 in regulating primary ciliogenesis, 13,20 it was somewhat unexpected that our previous study in RPE‐1 cells suggested that both remaining EHD paralogs, EHD4 and EHD2, appeared to be dispensable for primary ciliogenesis. Whereas EHD2 is an “outlier” with the least sequence identity and functional homology within the EHD‐family proteins, 37 EHD4 coordinates endosomal fission and recycling through its interactions with EHD1 29,30 and thus we initially chose to more extensively evaluate its potential role in regulating generation of the primary cilium.…”
Section: Resultsmentioning
confidence: 99%
“…EHD4 hetero-oligomerizes with EHD1 and appears to partially overlap in function with EHD1 and EHD3 in endosomal regulation. 29,30 EHD2, the most disparate EHD protein family member, binds to phosphatidylinositol(4,5)-bisphosphate, localizes to the plasma membrane, [31][32][33] and is involved in caveolae stabilization. 34,35 Despite the crucial roles of both EHD1 and EHD3 in the regulation of primary ciliogenesis, initial studies using the human RPE-1 cells suggested that both EHD2 and EHD4 may be dispensable for mammalian primary ciliogenesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…EH-containing and EH-interacting proteins are often implicated in the regulation of intracellular trafficking as well as cell signaling. 7,21,[26][27][28][29] Known EH domain containing proteins in humans are Eps15, Eps15R, intersectin 1 and 2, Reps1, POB1, Eps15 Homology Domain protein (EHD)1-4 and γ-synergin. Many of the listed proteins have been extensively studied in the past, but less is known about γ-synergin.…”
Section: Introductionmentioning
confidence: 99%
“…EHD4/Pincher mediates macropinocytosis required for retrograde endosomal Trk signaling ( 17, 18 ). EHD4 also recruits EHD1 to sorting endosomes via hetero-dimerization ( 19 ). Most recently, a role of an EHD4 complex in the trafficking of vascular endothelial cadherin (VE-cadherin) during angiogenesis was revealed ( 20 ).…”
Section: Introductionmentioning
confidence: 99%